2016
DOI: 10.1073/pnas.1520613113
|View full text |Cite
|
Sign up to set email alerts
|

Tracking brain arousal fluctuations with fMRI

Abstract: Changes in brain activity accompanying shifts in vigilance and arousal can interfere with the study of other intrinsic and task-evoked characteristics of brain function. However, the difficulty of tracking and modeling the arousal state during functional MRI (fMRI) typically precludes the assessment of arousal-dependent influences on fMRI signals. Here we combine fMRI, electrophysiology, and the monitoring of eyelid behavior to demonstrate an approach for tracking continuous variations in arousal level from fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
309
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(341 citation statements)
references
References 71 publications
30
309
2
Order By: Relevance
“…However, unlike prior studies, which largely relied on variations of depth of anesthesia, our comparison of awake states and anesthesia also suggested that the visual networks and their connectivity with default and frontoparietal networks actually showed anesthesia-related increases in connectivity. Overall, these findings echo recent studies of the impact of anesthetics on brain differences in humans, which suggested a loss of complexity in the functional architecture of the brain (Chang et al, 2016; Hutchison et al., 2014; Peltier et al, 2005; Smith et al, 2017; Wu et al, 2016). Further work will be required to rule out other possibilities, such as differences in respiration associated with differing states (awake or anesthesia).…”
Section: Discussionsupporting
confidence: 86%
“…However, unlike prior studies, which largely relied on variations of depth of anesthesia, our comparison of awake states and anesthesia also suggested that the visual networks and their connectivity with default and frontoparietal networks actually showed anesthesia-related increases in connectivity. Overall, these findings echo recent studies of the impact of anesthetics on brain differences in humans, which suggested a loss of complexity in the functional architecture of the brain (Chang et al, 2016; Hutchison et al., 2014; Peltier et al, 2005; Smith et al, 2017; Wu et al, 2016). Further work will be required to rule out other possibilities, such as differences in respiration associated with differing states (awake or anesthesia).…”
Section: Discussionsupporting
confidence: 86%
“…The utility of using SEC in the context of fMRI recordings was recently explored in two studies. The first study documented differences in resting-state fMRI global signal amplitude between eyes-open and eyes-closed states to EEG vigilance (50), and the second study documented fMRI BOLD signal fluctuations to eye-closure and invasive electrophysiological recordings in primates (51). Although relevant and buttressing the claims made here, these studies did not specifically address the triune relationship between fMRI DFC, eyelid status, and vigilance behavior documented here.…”
Section: Discussionmentioning
confidence: 78%
“…A recent finding regarding the global fMRI signal SD indicates that indeed the arousal of the subjects may have a widespread effect on the fMRI results (Chang et al., 2016; Liu et al., 2018). Subjects with epilepsy have altered sleep homeostasis and present widespread and complex neural and hemodynamic signal changes that are different in deep brain structures compared to cortex (Boly et al., 2017; Peter‐Derex, Magnin, & Bastuji, 2015; Salek‐Haddadi et al., 2003).…”
Section: Discussionmentioning
confidence: 99%